Nature of errors and mistakes in the English writings of graduating students in Bangladesh: A case study - Hoque, Muhammad Azizul; Alam, Md Morshedul; Ahmed, Hossain (IIUC Studies, 2020)
There is no denying that writing is quite tiresome in both second language teaching and learning situations. And so, selecting an appropriate strategy to provide the learners with necessary feedback in their writings seems to be a complicated task in language pedagogy. The present researchers observe that despite the writing practice of English for about 12 years in Bangladesh, the tertiary students commit mistakes and errors. They, therefore, feel numerous studies should be conducted to find an effective means of feedback for mistakes and errors the students make. Thus, this paper identifies the nature of mistakes and errors in their writings and finds out remedial procedures by means of knowing the factors contributing to the recurrence of these errors and mistakes year after year. To obtain data, some writing samples of paragraphs in groups, business letters, and letters of application have been taken from some undergraduate students of a university, and an opinion survey of teachers with an open-ended questionnaire has also been conducted. The study concludes with some pedagogical recommendations based on relevant concerns. IIUC Studies Vol.15(0) December 2018: 11-22